Exploring the Role of Emotional Intelligence in Leadership Effectiveness: A Qualitative Study - Grace Yulianti; Mohammad Chaidir; Dadang Irawan (LPPM STIE Kasih Bangsa, 2024)
This qualitative study delves into the pivotal role of emotional intelligence (EI) in enhancing leadership effectiveness. Through in-depth interviews and thematic analysis, the research investigates how leaders' emotional intelligence influences their ability to navigate complex interpersonal dynamics, inspire teams, and drive organizational success. Findings underscore the significance of EI competencies such as self-awareness, empathy, and relationship management in shaping leaders' decision-making processes and fostering a positive work environment. Moreover, the study reveals the nuanced ways in which emotionally intelligent leaders adapt their communication styles and cultivate trust and collaboration within their teams. By illuminating the intricate interplay between emotional intelligence and leadership effectiveness, this research offers valuable insights for organizations seeking to develop and nurture emotionally intelligent leaders capable of meeting the demands of today's dynamic workplace environments.